Settlement pattern and occupation shift among salt farmers - Merlia Indah Prastiwi (Faculty of Social and Political Science, Universitas Airlangga, 2019)
Madura can be seen as a microcosm of Indonesia as a whole through the various livelihoods of the Madurese people. Madura consists of people living along coastlines and this can be considered as representative of most Indonesian people. The primary occupations of the Madurese people are that of salt farmers and fishermen. Salt as a commercial business is cultivated by the community, is mostly located along the eastern and southern coastlines of Madura, and is adjusted to various circumstances, including lower rainfall in the area. During the rainy season, salt ponds are turned into shrimp ponds and farmers’ occupations change accordingly. The job of a salt farmer is not trouble-free. Problems arise from the erratic and uncertain climate and there are also threats of price instability and imported salt. Farmers are forced to accept such circumstances. This study contributes to the literature by exploring how the livelihood of salt farmers is representative of Indonesian’s maritime characteristics. Ironically, this sector has been increasingly abandoned and has become less desirable, though it plays a strategic industrial role in Indonesia. This study employed a qualitative method and determined its sample using the purposive sample technique. The informants were permanent salt farmers, salt farmers who also worked as shrimp farmers, and salt farmers who completely shifted to shrimp farming. This research was conducted in Lapak Daya, Dungkek, Sumenep. The findings showed that most salt farmers shifted their occupations to shrimp farmers because they considered it to be more profitable. However, some salt farmers who continued to survive in salt farming worked both as salt farmers and shrimp farmers. It was also found that salt farmers generally came from outside Madura, while those from Madura preferred changing their livelihood to farming shrimp due to the higher yields and the fact that the farming does not depend on seasonal changes. Although the number of salt farmers continues to decrease, there are some salt farmers who keep their occupation permanently.